Novel near-infrared ultrathin fluorescent glass and preparation method thereof
The preparation of Cr3+ activated oxide nanocrystals A3B2C3O12 in the ceramic casting molding process has solved the problem of insufficient development of near-infrared fluorescent materials in the existing technology, and achieved the preparation of high-efficiency near-infrared ultra-thin fluorescent glass, with wide applications Prospects and simple production process.
Patent Information
- Application Number
- CN202411546414.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-14
AI Technical Summary
The existing near-infrared fluorescent materials have insufficient development in expanding their application fields, especially in the preparation of high-efficiency near-infrared ultra-thin fluorescent glasses.
Cr3+ activated oxide nanocrystal A3B2C3O12 is used as the near-infrared luminescent component, and high-light efficiency near-infrared ultra-thin fluorescent glass is prepared by ceramic casting and low-temperature co-firing process. This material can achieve high-light-efficient near-infrared fluorescence under 470nm blue light excitation, and the emission peak can be adjusted within the range of 750-810nm.
It realizes the emission of high-light efficiency near-infrared fluorescence, has good physical properties and mechanical strength, is suitable for commercial ultraviolet and blue light LED chips, has broad market application prospects, and is simple and environmentally friendly in preparation, suitable for large-scale mass production.
Smart Images

Figure CN119430664A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of advanced luminescent materials and relates to a novel ultra-thin glass, in particular to a Cr 3+ Activated oxide nanocrystals A3B2C3O 12 Near-infrared ultra-thin glass (A=Ca, La, Y, Lu; B=Sc, Al; C=Ga, Sc, Si) and a preparation method thereof. Background Art
[0002] At present, as the light source of near-infrared detection devices, fluorescent conversion LED uses blue light chips to excite near-infrared fluorescent materials. It has the advantages of being simple and environmentally friendly, stable luminescence, and high efficiency, and has become the main research direction of near-infrared light sources. Near-infrared fluorescent materials can emit near-infrared light, have strong biological tissue penetration ability, and can avoid spontaneous fluorescence interference. Therefore, near-infrared luminescent materials are widely used in optical fiber communications, night vision displays, biological imaging, component analysis, fluorescent anti-counterfeiting, security monitoring, food and medicine testing, and other fields.
[0003] Compared with traditional near-infrared phosphors, near-infrared fluorescent glass has broad application prospects in many fields due to its advantages of broadband emission, good stability, high-efficiency conversion, controllability and environmental protection. However, according to existing research data, the development of near-infrared fluorescent glass is relatively scarce, which is of great significance for expanding research in this field. Therefore, the present invention discloses Cr 3+ The chemical formula of activated oxide is A3B2C3O 12 The invention relates to a near-infrared fluorescent glass (A=Ca, La, Y, Lu; B=Sc, Al; C=Ga, Sc, Si) and a preparation method thereof. On the basis of synthesizing nano-scale near-infrared fluorescent powder, a suitable ratio of glass powder is used to prepare near-infrared ultra-thin fluorescent glass with good physical properties and high light efficiency. Summary of the invention
[0004] One of the purposes of the present invention is to provide a near-infrared nanocrystalline A3B2C3O 12 :xCr 3+ (A=Ca, La, Y, Lu; B=Sc, Al; C=Ga, Sc, Si) preparation method of ultrafine powder.
[0005] The second purpose of the present invention is to provide a method for preparing a novel near-infrared ultra-thin fluorescent glass, which can achieve near-infrared emission with high light efficiency, is simple and environmentally friendly, and can be mass-produced.
[0006] In order to achieve the above-mentioned purpose, the technical scheme adopted by the present invention is as follows: a novel near-infrared ultra-thin fluorescent glass and a preparation method thereof, wherein the near-infrared fluorescent glass mainly uses a compound component with a molar ratio of a1% SiO2-a2% B2O3-a3% P2O5-a4% Al2O3-a5% BaO-a6CaO-a7% K2O as a glass matrix, and uses Cr 3+ Doped garnet-structured oxide fluorescent nanocrystals, A3B2C3O 12 :xCr 3+ (A = Ca, La, Y, Lu; B = Sc, Al; C = Ga, Sc, Si) as near-infrared luminescent components, prepared by ceramic tape casting combined with low-temperature co-firing process. The chemical formula of near-infrared phosphor is La3Sc 2-x Ga3O 12 :xCr 3+ , 0.01≤x≤1, where x is Cr 3+ Replace Sc 3+ The mole percentage of the bit.
[0007] The new ultra-thin fluorescent glass provided by the present invention can realize high-efficiency near-infrared fluorescence under 470nm blue light excitation, and the emission peak can be adjusted within the range of 750-810nm. The ultra-thin fluorescent glass can be used as a new near-infrared luminescence conversion material, and has good application prospects in improving the conversion efficiency of solid laser lamp pumps, promoting plant growth lighting and biomedical imaging.
[0008] On the other hand, the present invention provides a method for preparing the novel near-infrared ultra-thin fluorescent glass, which specifically comprises the following steps:
[0009] (1) According to the chemical formula La3Sc 2-x Ga3O 12 :xCr 3+ , the stoichiometric ratio of each element in 0.01≤x≤1 is respectively weighed La2O3, Sc2O3, Ga2O3, and (CH3COO)3Cr with a purity greater than 99% as raw material powders.
[0010] (2) Weigh a certain amount of concentrated nitric acid into a beaker, mix with deionized water and stir evenly to obtain a diluted nitric acid solution, pour the Ga2O3, La2O3, Sc2O3, and (CH3COO)3Cr powders weighed in step (1) into the diluted nitric acid solution in turn, stir thoroughly under heating conditions, and obtain a clear nitrate solution S1 containing the desired different metal ions.
[0011] (3) Weigh an appropriate amount of urea and ammonium bicarbonate powder into a beaker, and add a certain amount of deionized water to mix thoroughly to form a precipitant solution S2.
[0012] (4) The solution S2 obtained in step (3) is slowly dripped into the solution S1 at a titration rate of 3 to 100 ml / min. After the titration is completed, the pH value of the solution should be controlled between 5 and 8 to obtain a light blue suspension S3.
[0013] (5) The suspension S3 obtained in step (4) is treated by vacuum filtration or centrifugation to obtain the desired filter cake, and the filter cake is repeatedly rinsed with deionized water for more than 3 times. The filtered filter cake is placed in an oven for drying, and the oven temperature is set to 50-150°C.
[0014] (6) Grinding the dried filter cake in step (5) into fine powder, calcining it in a high temperature furnace at a temperature of 1300 to 1650° C. for 2 to 15 hours, and then cooling the powder to room temperature to obtain the desired LSG:Cr near-infrared nano-phosphor.
[0015] (7) The near-infrared nano-phosphor obtained in step (6) and the medium-temperature glass powder are accurately weighed according to a certain mass fraction ratio and placed in a ball mill, and an organic solvent and an additive are added. After mixing by ball milling, a glass slurry with excellent rheological properties is obtained.
[0016] (8) The slurry obtained in step (7) is subjected to high-speed centrifugal degassing treatment to obtain a mixed slurry with good consistency, and then subjected to a tape casting process to obtain an ultra-thin fluorescent glass blank.
[0017] (9) The green body obtained in step (8) is placed in a Mach furnace or a tubular furnace for low-temperature co-sintering treatment at a temperature of 450° C. to 850° C. for a sintering time of 0.5 h to 5 h. After sintering, the green body is naturally cooled to room temperature to obtain LSG:Cr near-infrared ultra-thin fluorescent glass.
[0018] Preferably, in step (2), the mass of the concentrated nitric acid is 1% to 10% of the total mass of the raw material powder, and the mass of the deionized water is 1 to 5 times the mass of the concentrated nitric acid. The stirring speed is 100 rpm to 1000 rpm, the heating temperature is 50° C. to 300° C., and the heating time is 3 h to 36 h.
[0019] Preferably, in step (3), the mass of the urea and ammonium bicarbonate powders is 0.8 to 1.5 times the total mass of the raw material powders, and the mass of the deionized water is 1 to 7 times the total mass of the urea and ammonium bicarbonate powders.
[0020] Preferably, in step (7), the organic solvent includes common organic liquids such as ethyl acetate, acetone, butanone, ethanol, toluene, xylene, etc. The auxiliary agent includes a dispersant, a binder, a plasticizer, etc.
[0021] Preferably, in step (8), the high-speed centrifugal degassing treatment has a rotation speed of 850 r / min to 2600 r / min, a vacuum degree of 5 to 130 KPa, and a time of 3 to 36 min.
[0022] Preferably, in step (9), the thickness of the ultra-thin fluorescent glass is in the range of 30 to 200 μm.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The near-infrared fluorescent material of the present invention has a classic garnet structure, the excitation range of the fluorescent material is 200 to 600 nm, and the emission spectrum covers a wide range of 650 to 900 nm. In particular, the particle size of the near-infrared fluorescent powder can reach the nanometer level, which provides a material basis for preparing near-infrared fluorescent glass with high light efficiency, and can be applied to commercial ultraviolet and blue light LED chips, and has broad market application prospects.
[0025] 2. The luminescence performance of the near-infrared fluorescent material of the present invention is adjustable. 3+ Activating the luminescence of different elements under the same structure has great research value, and its emission peak can be adjusted in the range of 750-810nm, which can be used as a fluorescent material for near-infrared LEDs for fluorescence conversion.
[0026] 3. The near-infrared ultra-thin fluorescent glass prepared by the present invention adopts the tape casting technology to achieve the uniform distribution of the near-infrared fluorescent powder in the glass matrix, and the prepared fluorescent glass also has good mechanical strength and heat dissipation performance. In addition, the fluorescent glass preparation method of the present invention has the advantages of simple operation, low cost, and suitability for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments with reference to the following drawings:
[0028] Figure 1 XRD diagrams of LSGC near-infrared phosphor and fluorescent glass obtained in Examples 1 and 3 of the present invention.
[0029] Figure 2 The excitation and emission spectra of the LSGC near-infrared ultra-thin fluorescent glass prepared in Example 3 of the present invention.
[0030] Figure 3 This is a scanning electron microscope image of the LSGC near-infrared nanocrystalline phosphor prepared in Example 1 of the present invention.
[0031] Figure 4 XRD diagrams of CSSC near-infrared phosphor and fluorescent glass obtained in Examples 4 and 5 of the present invention.
[0032] Figure 5 This is the excitation and emission spectra of the CSSC near-infrared ultra-thin fluorescent glass prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0034] It should be pointed out that the following examples will help those skilled in the art to further understand the present invention, but will not limit the present invention in any form.
[0035] Example 1
[0036] The preparation chemical formula is La3Sc 1.99 Ga3O 12 :0.01Cr 3+ Near-infrared nanocrystalline phosphors.
[0037] (1) According to the chemical formula La3Sc 1.99 Ga3O 12 :0.01Cr 3+ The stoichiometric ratio of each element in the mixture is as follows: Ga2O3, La2O3, Sc2O3, and (CH3COO)3Cr with a purity greater than 99% are weighed as raw material powders, added into the diluted concentrated nitric acid solution in sequence, placed on a magnetic stirrer and heated to 80°C at a speed of 480 rpm for 20 hours. When the solution becomes clear, a nitrate solution S1 containing the required different metal ions is obtained.
[0038] (2) Weigh urea and ammonium bicarbonate of equal total mass of the raw material powders respectively, and then pour deionized water of equal total mass of urea and ammonium bicarbonate into them and mix thoroughly to form a precipitant solution S2. The precipitant solution S2 is slowly dripped into the nitrate solution S1 obtained in the above (1) at a titration rate of 30 ml / min. After titration, the pH value of the detection solution should be controlled at about 7 to obtain a light blue suspension S3.
[0039] (3) The suspension S3 obtained in (2) is vacuum filtered to obtain a filter cake, which is repeatedly rinsed with deionized water, then dried and ground, and then calcined at high temperature for 10 hours. After completion, it is ground into fine powder to obtain the desired LSG:Cr (LSGC) near-infrared nanocrystalline phosphor.
[0040] like Figure 1 As shown, the La3Sc prepared in this example 1.99 Ga3O 12 :0.01Cr 3+ Near-infrared nanocrystalline phosphor, its XRD diffraction peak can be well compared with La3Sc2Ga3O 12This shows that the synthesized phosphor is pure phase, Cr 3+ Doping into the matrix does not destroy the crystal structure. Figure 3 As shown, the La3Sc prepared in this example 1.99 Ga3O 12 :0.01Cr 3+ Under the observation of scanning electron microscope, it can be found that the crystal particle size of near-infrared phosphor is much smaller than 1 micron, which has reached the nano-level ultrafine crystal powder, providing material support for the preparation of high-light-efficiency near-infrared ultra-thin fluorescent glass.
[0041] Example 2
[0042] The preparation chemical formula is La3Sc 1.98 Ga3O 12 :0.02Cr 3+ Near-infrared nanocrystalline phosphors.
[0043] (1) According to the chemical formula La3Sc 1.98 Ga3O 12 :0.02Cr 3+ The stoichiometric ratio of each element in the mixture is as follows: Ga2O3, La2O3, Sc2O3, and (CH3COO)3Cr with a purity greater than 99% are weighed as raw material powders, added into the diluted concentrated nitric acid solution in sequence, placed on a magnetic stirrer and heated to 80°C at a speed of 480 rpm for 20 hours. When the solution becomes clear, a nitrate solution S1 containing the required different metal ions is obtained.
[0044] (2) Weigh urea and ammonium bicarbonate of equal total mass of the raw material powders respectively, and then pour deionized water of equal total mass of urea and ammonium bicarbonate into them and mix thoroughly to form a precipitant solution S2. The precipitant solution S2 is slowly dripped into the nitrate solution S1 obtained in the above (1) at a titration rate of 30 ml / min. After titration, the pH value of the detection solution should be controlled at about 7 to obtain a light blue suspension S3.
[0045] (3) The suspension S3 obtained in (2) is vacuum filtered to obtain a filter cake, which is repeatedly rinsed with deionized water, then dried and ground, and then calcined at high temperature for 10 hours. After completion, it is ground into fine powder to obtain the desired La3Sc 1.98 Ga3O 12 :0.02Cr 3+ Near-infrared nanocrystalline phosphor.
[0046] Example 3
[0047] The preparation chemical formula is La3Sc 1.99 Ga3O 12 :0.01Cr 3+Near-infrared ultra-thin fluorescent glass.
[0048] (1) The LSG:Cr near-infrared nanocrystalline phosphor obtained in Example 1 and a suitable glass powder are accurately weighed according to a mass fraction ratio and placed in a ball mill, and an organic solvent and an additive are added. After ball milling and mixing, a glass slurry with excellent rheological properties is obtained.
[0049] (2) The glass slurry obtained in the above (1) was subjected to high-speed centrifugal degassing treatment at a rotation speed of 2000 r / min, a vacuum degree of 10 KPa, and a degassing time of 360 s to obtain a mixed slurry with good consistency.
[0050] (3) The mixed slurry obtained in the above (2) is subjected to a tape casting process to obtain a near-infrared fluorescent glass blank, which is placed in a tubular furnace at a temperature of 720° C. for low-temperature co-sintering for 2 hours, and naturally cooled to room temperature to obtain a near-infrared ultra-thin fluorescent glass with a thickness of only 83 μm.
[0051] like Figure 1 As shown, the La3Sc obtained in this example 1.99 Ga3O 12 :0.01Cr 3+ The XRD of the near-infrared ultra-thin fluorescent glass measured by the XRD, its main diffraction peak can be well compared with La3Sc2Ga3O 12 This indicates that the introduced glass component does not corrode Cr 3+ Activated La3Sc2Ga3O 12 The crystal structure of near-infrared phosphors, the fluorescent glass prepared from them can still retain the characteristics of efficient near-infrared luminescence. Figure 2 As shown, under 795nm monitoring, the excitation spectrum of the fluorescent glass contains two wide excitation bands in the wavelength range of 200-640nm. Under 470nm excitation, the maximum peak of the near-infrared emission band of the fluorescent glass can be observed at 795nm, which shows that the ultra-thin fluorescent glass can be used as a new type of near-infrared luminescence conversion material, and has good application prospects in improving the conversion efficiency of solid-state laser lamp pumps, promoting plant growth lighting and biomedical imaging.
[0052] Example 4
[0053] The chemical formula for preparation is Ca3Sc 1.94 SiO 12 :0.06Cr 3+ Near-infrared nanocrystalline phosphors.
[0054] (1) According to the chemical formula Ca3Sc 1.94 SiO 12 :0.06Cr 3+The stoichiometric ratio of each element in the mixture is as follows: SiO2, CaCO3, Sc2O3, and (CH3COO)3Cr with a purity greater than 99% are weighed as raw material powders, added into the diluted concentrated nitric acid solution in sequence, placed on a magnetic stirrer and heated to 80°C at a speed of 480 rpm for 20 hours. When the solution becomes clear, a nitrate solution S1 containing the required different metal ions is obtained.
[0055] (2) Weigh urea and ammonium bicarbonate of equal total mass of the raw material powders respectively, and then pour deionized water of equal total mass of urea and ammonium bicarbonate into them and mix thoroughly to form a precipitant solution S2. The precipitant solution S2 is slowly dripped into the nitrate solution S1 obtained in the above (1) at a titration rate of 30 ml / min. After the titration, the pH value of the detection solution should be controlled at about 7 to obtain a suspension S3.
[0056] (3) The suspension S3 obtained in the above (2) is vacuum filtered to obtain a filter cake, which is repeatedly rinsed with deionized water, then dried and ground, and then calcined at high temperature for 10 hours. After completion, it is ground into fine powder to obtain the desired CSS:Cr (CSSC) near-infrared nanocrystalline phosphor.
[0057] like Figure 4 As shown, the Ca3Sc prepared in this example 1.94 SiO 12 :0.06Cr 3+ Near-infrared nanocrystalline phosphor, its XRD diffraction peak can be well compared with Ca3Sc2Si3O 12 This shows that the synthesized phosphor is pure phase, Cr 3+ Doping into the matrix will not destroy the crystal structure, providing a material basis for the preparation of high-efficiency near-infrared ultra-thin fluorescent glass.
[0058] Example 5
[0059] The chemical formula for preparation is Ca3Sc 1.94 SiO 12 :0.06Cr 3+ Near-infrared ultra-thin fluorescent glass.
[0060] (1) The CSS:Cr near-infrared nanocrystalline phosphor obtained in Example 4 and a suitable glass powder are accurately weighed according to a mass fraction ratio and placed in a ball mill, and an organic solvent and an additive are added. After ball milling and mixing, a glass slurry with excellent rheological properties is obtained.
[0061] (2) The glass slurry obtained in the above (1) was subjected to high-speed centrifugal degassing treatment at a rotation speed of 2000 r / min, a vacuum degree of 10 KPa, and a degassing time of 360 s to obtain a mixed slurry with good consistency.
[0062] (3) The mixed slurry obtained in the above (2) is subjected to a tape casting process to obtain a near-infrared fluorescent glass blank, which is placed in a tubular furnace at a temperature of 720° C. for low-temperature co-sintering for 2 hours, and naturally cooled to room temperature to obtain a near-infrared ultra-thin fluorescent glass with a thickness of only 78 μm.
[0063] like Figure 4 As shown, the Ca3Sc obtained in this example 1.94 SiO 12 :0.06Cr 3+ The XRD of the near-infrared ultra-thin fluorescent glass measured by the XRD, its main diffraction peak can be well compared with Ca3Sc2Si3O 12 This indicates that the introduced glass component does not corrode Cr 3+ Activated Ca3Sc2Si3O 12 The crystal structure of near-infrared nanocrystalline phosphors, the ultra-thin fluorescent glass prepared from it can still retain the characteristics of efficient near-infrared luminescence. Figure 5 As shown, under 762nm monitoring, the excitation spectrum of the fluorescent glass has a wide excitation band in the wavelength range of 350-550nm. Under 470nm excitation, the maximum peak of the near-infrared emission band of the fluorescent glass can be observed at 762nm, which shows that the ultra-thin fluorescent glass can be used as a new type of near-infrared luminescence conversion material, and has good application prospects in improving the conversion efficiency of solid-state laser lamp pumps, promoting plant growth lighting and biomedical imaging.
[0064] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent substitution, improvement and supplement made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A novel near-infrared ultra-thin fluorescent glass and its preparation method, the key features of which specifically include the following four aspects: (1) Ultrafine nanoscale near-infrared phosphor oxide A3B2C3O 12 :xCr 3+ Synthesis of (A=Ca, La, Y, Lu; B=Sc, Al; C=Ga, Sc, Si). (2) Select appropriate medium-temperature transparent glass powder and prepare a mixed slurry of glass and phosphor. (3) The thin film casting forming process and low-temperature co-firing technology of the glass slurry. (4) The substrate peeling technology of the ultra-thin fluorescent glass.
2. The novel near-infrared ultra-thin fluorescent glass and its preparation method according to claim 1, characterized in that: The chemical formula of the near-infrared phosphor is A3B2C3O 12 :xCr 3+ (A = Ca, La, Y, Lu; B = Sc, Al; C = Ga, Sc, Si), where 0 < x < 1, and the mass percentage of the phosphor in the fluorescent glass is 0.1% - 50%.
3. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 1, characterized in that: The composition of the appropriate glass powder is: a1% SiO2 - a2% B2O3 - a3% P2O5 - a4% Al2O3 - a5% BaO - a6 CaO - a7% K2O, where 0 < a1 < 100, 0 < a2 < 100, 0 < a3 < 100, 0 < a4 < 100, 0 < a5 < 100, 0 < a6 < 100, 0 < a7 < 100, and a1 + a2 + a3 + a4 + a5 + a6 + a7 = 100.
4. A novel near-infrared ultra-thin fluorescent glass and a preparation method thereof as claimed in claim 1, characterized in that: Specifically, it includes the following steps: (1) According to the chemical formula La3Sc 2-x Ga3O 12 :xCr 3+ , the stoichiometric ratio of each element in 0.01≤x≤1 is respectively weighed La2O3, Sc2O3, Ga2O3, and (CH3COO)3Cr with a purity greater than 99% as raw material powders. (2) Weigh a certain amount of concentrated nitric acid and pour it into a beaker, mix it with deionized water and stir evenly to obtain a diluted nitric acid solution. Pour the Ga2O3, La2O3, Sc2O3, and (CH3COO)3Cr powders weighed in step (1) into the diluted nitric acid solution in turn, and stir well under heating conditions to obtain a clear nitrate solution S1 containing the required different metal ions. (3) Weigh an appropriate amount of urea and ammonium bicarbonate powders and put them into a beaker, and add a certain amount of deionized water to mix well to form a precipitant solution S2. (4) Slowly drip the solution S2 obtained in step (3) into the solution S1, with a titration speed of 3 - 100 ml / min. After titration, the pH value of the solution should be controlled between 5 and 8 to obtain a light blue suspension S3. (5) Treat the suspension S3 obtained in step (4) by vacuum filtration or centrifugation to obtain the required filter cake. Rinse the filter cake repeatedly with deionized water, with the number of rinses > 3 times. Put the filter cake after vacuum filtration into an oven for drying, and set the oven temperature to 50 - 150 °C. (6) Grind the dried filter cake in step (5) into fine powder, perform calcination treatment in a high-temperature furnace, with a calcination temperature of 1300 - 1650 °C and a calcination time of 2 - 15 h. Wait for it to cool to room temperature and grind the powder to obtain the required LSG:Cr near-infrared nano-fluorescent powder. (7) Weigh the near-infrared nano-fluorescent powder obtained in step (6) and the medium-temperature glass powder according to a certain mass fraction ratio, place them in a ball mill tank, add organic solvents and additives, and obtain a glass slurry with excellent rheological properties through ball milling and mixing. (8) Subject the slurry obtained in step (7) to high-speed centrifugal defoaming treatment to obtain a well-consistent mixed slurry, and obtain an ultra-thin fluorescent glass green body through the thin film casting forming process. (9) Place the green body obtained in step (8) in a muffle furnace or tube furnace for low-temperature co-sintering treatment, with a temperature of 450 °C - 850 °C and a sintering time of 0.5 h - 5 h. After sintering, let it cool naturally to room temperature to obtain the LSG:Cr near-infrared ultra-thin fluorescent glass.
5. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 4, characterized in that: In step (2), the mass of the concentrated nitric acid is 1% to 10% of the total mass of the raw material powder, and the mass of the deionized water is 1 to 5 times the mass of the concentrated nitric acid. The stirring speed is 100 rpm to 1000 rpm, the heating temperature is 50° C. to 300° C., and the heating time is 3 h to 36 h.
6. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 4, characterized in that: In step (3), the mass of the urea and ammonium bicarbonate powders is 0.8 to 1.5 times the total mass of the raw material powders, and the mass of the deionized water is 1 to 7 times the total mass of the urea and ammonium bicarbonate powders.
7. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 4, characterized in that: In step (7), the organic solvent includes common organic liquids such as ethyl acetate, acetone, butanone, ethanol, toluene, xylene, etc. The auxiliary agent includes a dispersant, a binder, a plasticizer, etc.
8. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 4, characterized in that: In step (8), the high-speed centrifugal degassing treatment has a rotation speed of 850 r / min to 2600 r / min, a vacuum degree of 5 to 130 KPa, and a time of 3 to 36 min.
9. The novel near-infrared ultra-thin fluorescent glass and the preparation method thereof according to claim 4, characterized in that: In step (9), the thickness of the near-infrared ultra-thin fluorescent glass ranges from 30 to 200 μm.
Citation Information
Patent Citations
Cr < 3 + > / Ni < 2 + > co-doped broadband near-infrared fluorescent powder, preparation method thereof and conversion type LED light-emitting device
CN114656955A
Broadband near-infrared luminescent material as well as preparation method and application thereof
CN116554865A
Preparation method of ultrathin nitride-based red fluorescent glass
CN118084337A
Oxide near-infrared luminescent glass ceramic material and preparation method thereof
CN118851574A